Comparative Growth Inhibition of Bread Spoilage Fungi by Different Preservative Concentrations Using a Rapid Turbidimetric Assay System - Garcia, Marcelo Valle; Garcia-Cela, Esther; Magan, Naresh; Copetti, Marina Venturini; Medina, Angel (Frontiers in Microbiology, 2021)
Bread and intermediate moisture bakery products are mainly spoiled by yeasts and filamentous fungi. The inoculum load and preservation system used determines their shelf-life. To extend the shelf-life of such commodities, the use of chemical preservatives is the most common way to try and control the initiation of mould spoilage of bread. This study has utilized a rapid turbidimetric assay system (Bioscreen C) to examine the temporal efficacy of calcium propionate (CP) and potassium sorbate (PS) for controlling the growth of important bread spoilage fungi. The objectives were to compare the temporal growth of strains of three important spoilage fungi (Hyphopichia burtonii (HB17), Paecilomyces variotii (PV11) and Penicillium roqueforti (PR06) isolated from visibly moulded bread to (a) different concentrations of CP and PS (0-128 mM), (b) temperatures (25, 30°C), (c) water activity (aw; 0.95, 0.97) and (d) pH (5.0, 5.5). All three abiotic factors, pH, aw, and temperature, and preservative concentrations influenced the relative growth of the species examined. In general, PS was more effective than CP in inhibiting the growth of the strains of these three species. In addition, the Time to Detection (TTD) for efficacy of the preservatives under the interacting abiotic factors was compared. The strain of P. variotii (PV10) was the most tolerant to the preservatives, with the shortest TTD values for both preservatives. P. roqueforti was the most sensitive with the longest TTD values under all conditions examined. These results are discussed in the context of the evolution of resistance to food-grade preservatives by such spoilage fungi in bakery products.